2021
DOI: 10.3390/jcm10153403
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic Approaches for Prediction of Therapeutic Responses in Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder in which, via unresolved mechanisms, platelets and megakaryocytes (MKs) are targeted by autoantibodies and/or T cells resulting in increased platelet destruction and impairment of MK function. Over the years, several therapeutic modalities have become available for ITP, however, therapeutic management has proven to be very challenging in several cases. Patients refractory to treatment can develop a clinically worsening disease course, treatment-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 93 publications
(163 reference statements)
0
16
0
Order By: Relevance
“…The authors aimed to analyse how beneficial this score was in their population for predicting ITP duration <6 months in 3 age groups: <12 months, 1–8 years, and over 9 years old. The choice of 6 months as predictive threshold was based on previous studies that found a high percentage of spontaneous remission after 6 months from diagnosis ( 5 , 9 , 13 , 21 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors aimed to analyse how beneficial this score was in their population for predicting ITP duration <6 months in 3 age groups: <12 months, 1–8 years, and over 9 years old. The choice of 6 months as predictive threshold was based on previous studies that found a high percentage of spontaneous remission after 6 months from diagnosis ( 5 , 9 , 13 , 21 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…While investigations into immune functions in ITP ( 7 , 8 ), aiming for a better prediction of platelet count responses have been exploited and included in nowadays ITP management ( 9 11 ), a lack of consensus among clinical scores and use in ITP monitoring still exists ( 10 ). Several clinical scores have been developed including a combination of different already known risk factors: age, gender, presence of a previous infections or vaccination, bleeding grade, type of onset, platelet count at diagnosis ( 1 , 12 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several miRNAs with significant immunological functions have been described to be up-or down regulated in ITP [81,[84][85][86]. Moreover, circulating miRNA levels have been observed to be increased or decreased after several ITP treatments, indicating that miRNA could be a possible biomarker for therapeutic response [30,87,88]. In this regard, one could hypothesize that PMP contents such as miRNAs might even differ between several subgroups of patients with ITP, including acute vs. chronic ITP and therapeutic responders vs. non-responders.…”
Section: The Different Cargos Of Itp-pmpsmentioning
confidence: 99%
“…Most importantly, the likely possibility that platelets are not only the victims of the autoimmune response in ITP, but also immuno-modulating cells involved in promoting and sustaining their own destruction, is an important issue which warrants further investigation. More understanding of the role of platelets in the pathophysiology of ITP could help us with identification of new diagnostic biomarkers and predictors of therapeutic response [87]. Ultimately, this may lead to new platelet-directed therapeutic strategies for ITP.…”
Section: Final Recommendationsmentioning
confidence: 99%
“…With updated guidelines recommending deferral of splenectomy, refractory ITP has been redefined to include those who are non‐responsive to ≥2 lines of therapy, lack of response to any therapy, or bleeding associated with severe thrombocytopaenia [10]. In these cases, management can be challenging as alternative therapeutic options are associated with lower response rates, immunosuppressive complications, treatment‐specific toxicities and poor durability of response [11].…”
Section: Introductionmentioning
confidence: 99%